Multiple acid‐base and electrolyte disturbances upregulate NBCn1, NBCn2, IRBIT and L‐IRBIT in the mTAL. (30th May 2020) - Wang, Jin‐Lin; Wang, Xiao‐Yu; Wang, Deng‐Ke; Parker, Mark D.; Musa‐Aziz, Raif; Popple, Jacob; Guo, Yi‐Min; Min, Tian‐Xin; Xia, Tian; Tan, Min; Liu, Ying; Boron, Walter F.; et al.
Abstract : Key points: The roles of the Na + /HCO3 – cotransporters NBCn1 and NBCn2 as well as their activators IRBIT and L‐IRBIT in the regulation of the mTAL transport of NH4 +, HCO3 –, and NaCl are investigated. Dietary challenges of NH4 Cl, NaHCO3 or NaCl all increase the abundance of NBCn1 and NBCn2 in the outer medulla. The three challenges generally produce parallel increases in the abundance of IRBIT and L‐IRBIT in the outer medulla. Both IRBIT and L‐IRBIT powerfully stimulate the activities of the mTAL isoforms of NBCn1 and NBCn2 as expressed in Xenopus oocytes. Our findings support the hypothesis that NBCn1, NBCn2, IRBIT and L‐IRBIT appropriately promote NH4 + shunting but oppose HCO3 – and NaCl reabsorption in the mTAL, and thus are at the nexus of the regulation pathways for multiple renal transport processes. Abstract: The medullary thick ascending limb (mTAL) plays a key role in urinary acid and NaCl excretion. NBCn1 and NBCn2 are present in the basolateral mTAL, where NBCn1 promotes NH4 + shunting. IRBIT and L‐IRBIT (the IRBITs) are two powerful activators of certain acid‐base transporters. Here we use western blotting and immunofluorescence to examine the effects of multiple acid‐base and electrolyte disturbances on expression of NBCn1, NBCn2 and the IRBITs in rat kidney. We also use electrophysiology to examine the functional effects of IRBITs on NBCn1 and NBCn2 in Xenopus oocytes. NH4 Cl‐induced metabolic acidosis (MAc) substantially increases protein expression of NBCn1 and NBCn2 in the outer medulla (OM) of rat kidney. Surprisingly, NaHCO3 ‐induced metabolic alkalosis (MAlk) and high‐salt diet (HSD) also increase expression of NBCn1 and NBCn2 (effect of NaHCO3  > HSD). Moreover, all three challenges generally increase OM expression of the IRBITs. In Xenopus oocytes, the IRBITs substantially increase the activities of NBCn1 and NBCn2. We propose that upregulation of basolateral NBCn1 and NBCn2 plus the IRBITs in the mTAL: (1) promotes NH4 + shunting by increasing basolateral HCO3 – uptake to neutralize apical NH4 + uptake during MAc; (2) inhibits HCO3 – reabsorption during MAlk by opposing HCO3 − efflux via the basolateral anion exchanger AE2; and (3) inhibits NaCl reabsorption by mediating (with AE2) net NaCl backflux into the mTAL cell during HSD. Thus, NBCn1, NBCn2 and the IRBITs are at the nexus of the regulatory pathways for multiple renal transport processes. Key points: The roles of the Na + /HCO3 – cotransporters NBCn1 and NBCn2 as well as their activators IRBIT and L‐IRBIT in the regulation of the mTAL transport of NH4 +, HCO3 –, and NaCl are investigated. Dietary challenges of NH4 Cl, NaHCO3 or NaCl all increase the abundance of NBCn1 and NBCn2 in the outer medulla. The three challenges generally produce parallel increases in the abundance of IRBIT and L‐IRBIT in the outer medulla. Both IRBIT and L‐IRBIT powerfully stimulate the activities of the mTAL isoforms of NBCn1 and NBCn2 as expressed in Xenopus oocytes. Our findings support the hypothesis that NBCn1, NBCn2, IRBIT and L‐IRBIT appropriately promote NH4 + shunting but oppose HCO3 – and NaCl reabsorption in the mTAL, and thus are at the nexus of the regulation pathways for multiple renal transport processes.